Multianálisis de las organizaciones más valoradas para el desempe\~no laboral en Espa\~na; Multi analysis of most valued companies for labour performance in Spain - Francisco J. Ferreiro-Seoane (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2020)
– The present article intends to study the profile of the most valued companies regarding their labour performance in Spain. It also tries to determine the influence that this profile's characteristics have on the overall rating. For that purpose, we analyse the 100 companies, taken from the ranking published by the Journal of Actualidad Económica (RAE in Spanish), with the highest value every year between 2013 and 2016. As first step, a descriptive analysis of the averaged valuations of the companies is made, grouping them by their nationality, the regions where the companies have their headquarters, their economic sector, their size and their market/share price. Secondly, using multiple regression models, the influence of these characteristics (as independent variables) on the total value (as a dependent variable) will be analyzed and quantified. Despite the studies carried out by some authors, none of them has analyzed objective variables of the companies to know their profiles and their possible influence on the total value. The main findings show that the majority of the most attractive companies have an international character (17 countries); also, that the predominant sectors are the financial ones and those that develop professional and scientific activities, located in the capital of the country (76.8%) with a big size and listed on the market. It concludes that only the size and the market/share price could influence the total valuation of the companies. We highlight as main contributions the newness of this type of study using quantitative methods and a higher knowledge of the profile of the most attractive companies to work for in Spain.
Keywords: J24; J28; M51; 330; companies; human resources; nationality; territory; autonomous community